Optimizing Engineering Problems Through Heuristic Techniques - Kumar, K. (Kaushik), 1968-; Zindani, Divya, 1989-; Davim, J. Paulo (Boca Raton : CRC Press LLC, 2019)
This book will cover heuristic optimization techniques and applications in engineering problems. The book will be divided into three sections that will provide coverage of the techniques, which can be employed by engineers, researchers, and manufacturing industries, to improve their productivity with the sole motive of socio-economic development. This will be the first book in the category of heuristic techniques with relevance to engineering problems and achieving optimal solutions. Features Explains the concept of optimization and the relevance of using heuristic techniques for optimal solutions in engineering problems Illustrates the various heuristics techniques Describes evolutionary heuristic techniques like genetic algorithm and particle swarm optimization Contains natural based techniques like ant colony optimization, bee algorithm, firefly optimization, and cuckoo search Offers sample problems and their optimization, using various heuristic techniques
7.1 Introduction7.2 Cuckoo Search Methodology; 7.3 Variants of Cuckoo Search Algorithm; 7.3.1 Adaptive Cuckoo Search Algorithm; 7.3.2 Self-Adaptive Cuckoo Search Algorithm; 7.3.3 Cuckoo Search Clustering Algorithm; 7.3.4 Novel Adaptive Cuckoo Search Algorithm; 7.3.5 Cuckoo Search Algorithm Based on Self-Learning Criteria; 7.3.6 Discrete Cuckoo Search Algorithm; 7.3.7 Differential Evolution and Cuckoo Search Algorithm; 7.3.8 Cuckoo Inspired Fast Search; 7.3.9 Cuckoo Search Algorithm Integrated with Membrane Communication Mechanism; 7.3.10 Master-Leader-Slave Cuckoo
Description based upon print version of record.
7.3.11 Cuckoo Search Algorithm with Wavelet Neural Network Model
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Database Management / Data Mining; MATHEMATICS / Probability & Statistics / Bayesian Analysis; TECHNOLOGY / Engineering / Industrial; Open systems (Physics)